Harvest-Induced Size Structure Shifts Alter Nutrient Release by a Population of Omnivorous Fish. Issue 3 (3rd May 2016) - Catalano, Matthew J.; Schaus, Maynard H.
Abstract: Fish body size can have important consequences for physiological factors, such as feeding, respiration, and nutrient excretion. Thus, the size structure of a fish population can greatly impact its role in lake nutrient cycles. We examined how shifts in body size influenced phosphorus cycling by Gizzard Shad Dorosoma cepedianum in Lake Dora, Florida, which underwent a size-selective fish harvest during 2005 and 2006. We combined a size-structured stock assessment model with excretion prediction coefficients to determine how shifts in population biomass and size distribution affected nutrient cycling. The harvest selectively removed larger Gizzard Shad, reducing the population biomass by 29.4% during the 2 years after removal, and shifted the population toward predominance by smaller size-classes. However, phosphorus excretion decreased by only 19.7% during this period because smaller fish excreted more P/g of body size. Three years following the harvest, biomass averaged 8.0% below the pre-harvest average, but phosphorus release returned to near the baseline average in approximately 1 year. Our results indicate that size shifts that accompany many biomanipulation efforts may offset some of the reductions in internal nutrient cycling. Received August 26, 2015; accepted January 11, 2016 Published online April 27, 2016